Assessment of root canal morphology of mandibular permanent anterior teeth in an Iraqi subpopulation by cone-beam computed tomography - Ranjdar mahmood talabani (Elsevier, 2021)
Background/purpose: Endodontic treatment is basically dependent on knowledge of the root canal anatomy. This study aimed to analyze the root canal configuration of mandibular anterior teeth in an Iraqi subpopulation using cone-beam computed tomography (CBCT) imaging. Materials and methods: A total of 305 CBCT scans involving 1794 mandibular permanent anterior teeth were evaluated. The number of roots, root canals, root canal system configuration according to Vertucci classification, and bilateral symmetry in root number and root canal number were recorded and statistically analyzed. The effects of gender and age on the incidence of root canal morphology and root canal number were investigated. Chi-square test was used to determine the level of significance (p < 0.05) and Kappa value was used to check reliability of results of the research. Results: Among the study patients, double root canals were found in (right 26.1% and left 26.4%) mandibular central incisors, in lateral incisors (right 28% and left 30.4%) and canines (right 11.7% and left 11%). Most teeth (77.8%) had a Type I Vertucci configuration and Type V was the least common and only present in canines (0.8%). All examined incisors presented with only one root and only around 2% of canines had two roots. Gender differences were identified for central incisors, while for lateral incisors and canines there were none. Patients older than 60 years had fewer teeth with double root canals (p < 0.05). Slight bilateral asymmetries appeared in central, lateral incisors, and canines in relation to root and root canal numbers. Conclusion: Single rooted with Type I canal configuration is the most prevalent in mandibular anterior teeth in the Iraqi subpopulation. However, the incidence of more than one root canal with different canal configurations is also detected.